Contact Mask Technique for Laser Structuring of 3-D MID - Roth, Stephan; Dietel, C.; Eßer, Gerd; Geiger, Manfred (Proceedings of the IEMT Europe Symposium, Electronics Manufacturing and Development for Automotives, 1998)
Molded Interconnect Devices (MID) are promising polymer parts for many industrial applications to make possible complex functional components containing circuits, and to avoid costs in material and production. Already existing examples in the automotive field are a car dash board and a rear stop light. For suitable large scale production technologies for complex three-dimensional MID, development of new manufacturing processes is essential. Different technologies are used to generate circuit patterns on the substrate by photoimaging. The geometrical information can be transformed by using different mask technologies. Besides the common mask projection technique, a contact mask which contains the circuit geometry is also suitable. Therefore the circuits are generated in original scale by IR laser radiation on a polyvinyl chloride (PVC) sheet. The blackened polymer is non-transparent for UV radiation of common UV lamps and especially excimer lasers, used for imaging of photosensitive resists. For three-dimensional masks the sheet is formed by a deep drawing process.
LFT Import::2019-08-05 (1618)